Antidiabetes activity of herbal product containing Phyllanthus niruri and Zingiber americans - Elfahmi; Adnyana, I Ketut; Fitria, Ika; Taufikurahman, Taufik (Penerbit Universiti Kebangsaan Malaysia, 2020)
The diabetes mellitus is one of the chronic diseases that has high prevalence rates in the world. It is defined as a state of hyperglycemia which usually accompanied by increasing blood glucose level. The combination of Phyllanthus niruri herbs and Zingiber americans rhizome has been produced as herbal medicine for the treatment of diabetes. The efficacy of combination of these plants is still based on empirical data. This research aimed to prove the antidiabetes activity of herbal medicine product containing P. niruri and Z. americans in vivo. Antidiabetes activity was tested using oral glucose tolerance and alloxan induced methods. The blood glucose levels were measured in each experiment. In addition, the plasma triglyceride and total cholesterol levels were also measured. The results showed that the decrease of blood glucose levels on oral glucose tolerance method were 40.98, 44.84, and 47.02% at doses of 90, 135, and 203 mg/kg BW, respectively (p <0.05) compared to control. While the decrease in blood glucose levels in alloxan induced method were 33.05, 38.82, and 41.79% at dose 90, 135, and 203 mg/kg BW, respectively (p <0.05) compared to control. The extract of dose 203 mg/kg BW appeared to be the most potent to decrease blood glucose levels in both methods, but did not show suppression activity of triglycerides and total cholesterol plasma. Suppression activities of serum triglycerides and total cholesterol were shown after treatment with the extract dose 90 and 135 mg/kg BW, which were significantly different to control (p < 0.05). The herbal product contains flavonoid, phenol and tannin, which total of each were 0.15, 0.16, and 1.85% w/w, respectively.